Rotation and decentration of an undersized plate-haptic trifocal toric intraocular lens in an eye with moderate myopia - Giers, Bert Constantin; Khoramnia, Ramin; Weber, Lea F.; Tandogan, Tamer; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2016)
We present the case of a 56-year-old woman with moderate myopia and bilateral cataract who had cataract extraction and intraocular lens (IOL) implantation. Due to the patient’s desire for spectacle independence, a trifocal IOL with toric correction for astigmatism was implanted. During the follow-up, it became obvious that the implanted IOL had rotated and tilted due to insufficient fixation in the large capsular bag of the myopic eye. An IOL explantation was therefore performed, and the original IOL was exchanged for a bifocal toric IOL with a larger overall diameter. Stable fixation of the IOL in the capsular bag was achieved, and after surgery in the second eye, the patient recovered good bilateral vision. This case illustrates the need for careful selection of IOL diameter and sizing even in patients with moderate myopia due to the potentially larger ocular dimensions in these patients. - Financial Disclosures - Drs. Auffarth, Tandogan, and Khoramnia received research grants, travel expenses, and lecture fees from Abbott Medical Optics, Inc. and Carl Zeiss Meditec AG. Drs. Giers and Weber have no financial or proprietary interest in any material or method mentioned.
Gesehen am 09.06.2020